2010
DOI: 10.1152/ajpendo.00723.2009
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus infection results in alterations of insulin signaling and glucose homeostasis

Abstract: Jiang S, Gavrikova TA, Pereboev A, Messina JL. Adenovirus infection results in alterations of insulin signaling and glucose homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
1
10
1
Order By: Relevance
“…2D and E). Recently, it has been reported that Ad-bgal injection in rat impaired glucose homeostasis at 4-6 days post-injection [16]. At both 7 and 14 days after Adbgal injection, no difference was noticed in glucose tolerance between saline-injected (control) and Ad-bgal-injected mice (data not shown).…”
Section: Liver Adenovirus-mediated Cpt1mt Expression Decreases Glucosmentioning
confidence: 78%
“…2D and E). Recently, it has been reported that Ad-bgal injection in rat impaired glucose homeostasis at 4-6 days post-injection [16]. At both 7 and 14 days after Adbgal injection, no difference was noticed in glucose tolerance between saline-injected (control) and Ad-bgal-injected mice (data not shown).…”
Section: Liver Adenovirus-mediated Cpt1mt Expression Decreases Glucosmentioning
confidence: 78%
“…10,11 Like other human adenoviruses, Ad36 downregulates IR, IRS1 or IRS2 activation, yet, Ad36 recruits the distal insulin signaling pathway (PI3K/AKT) via Ras activation, leading to greater Glut4 abundance and translocation and glucose disposal. 911,13 …”
Section: Introductionmentioning
confidence: 99%
“…Liver tissues from each animal were homogenized in lysis buffer, as described previously (11,13,16,22). The tissue lysates were centrifuged, and the supernatants were stored at Ϫ80°C until use.…”
Section: Methodsmentioning
confidence: 99%
“…The recombinant adenovirus vector expressing a dominant negative mutant (T183A/Y185F) of JNK1 (Ad-DN-JNK1) was purchased from Cell Biolabs (San Diego; ADV-115) and was rendered kinase dead by two mutations within the JNK kinase domain. The Ad vectors were amplified in 293A cells and purified twice by cesium chloride gradient ultracentrifugation followed by dialysis (11,13). The biological titer [plaque forming units (pfu)/ml] was determined by the TCID50 (tissue culture infectious dose 50) method (Adenovector Vector System) based on the development of a cytopathic effect in 293 cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation